Pelatihan Pembuatan Kerajinan dengan Bahan Dasar Tulang Daun melalui Proses Dekomposisi - Devi Anugrah; Hilman Faruq; Susilo Susilo (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The 2013 curriculum requires learning materials to improve the competence of knowledge, skills, and attitudes to create valuable work. This decomposed leaf bone handicraft activity is a concrete example of fulfilling 2013 curriculum achievements. Besides helping to understand biology lessons, the activity of making leaf bone crafts can foster an entrepreneurial spirit for students. Therefore, in this community service activity, training to make handicrafts from leaf bones is given to teachers and students in SMA N 1 and SMP 2 Banyuputih, Situbondo. The training was attended by 23 students and one teacher at SMA N 1 and dam 20 students and one teacher at SMP 2 Banyuputih, Situbondo. The training is carried out by the method of delivering material and direct practice. The activity was also carried out with direct discussion with participants. The results of this training activity showed that all participants gained new knowledge and skills, namely how to make crafts made from leaf bones. Craft made of leaf bone is very attractive to students because students can know the bone structure directly. This dedication activity provides insight to both students and teachers to take advantage of local wisdom around it to be more valuable.